2019
DOI: 10.1371/journal.pgen.1008077
|View full text |Cite
|
Sign up to set email alerts
|

Novel AU-rich proximal UTR sequences (APS) enhance CXCL8 synthesis upon the induction of rpS6 phosphorylation

Abstract: The role of ribosomal protein S6 (rpS6) phosphorylation in mRNA translation remains poorly understood. Here, we reveal a potential role in modulating the translation rate of chemokine (C-X-C motif) ligand 8 ( CXCL8 or Interleukin 8, IL8 ). We observed that more CXCL8 protein was being secreted from less CXCL8 mRNA in primary macrophages and macrophage-like HL-60 cells relative to other cell types. This correlated with an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…10, shadowed in the rectangle), suggesting that the conserved activation/inactivation mechanism might rely on these two residues. On the other side, human Bin2 is also (43)(44)(45). In the present study, we showed that Bin2 might be a novel kinase that directly phosphorylates RPS6 (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…10, shadowed in the rectangle), suggesting that the conserved activation/inactivation mechanism might rely on these two residues. On the other side, human Bin2 is also (43)(44)(45). In the present study, we showed that Bin2 might be a novel kinase that directly phosphorylates RPS6 (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Conceivably, it can regulate various important cellular processes. Actually, RPS6 is known to be regulated by multiple kinases and phosphatases (43)(44)(45). In the present study, we showed that Bin2 might be a novel kinase that directly phosphorylates RPS6 (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, a decrease in the phosphorylation of S6, consistent with control of proliferation was detected after DLG2 overexpression. Decreased S6 phosphorylation has been shown to inhibit the synthesis of the chemokine IL-8 (Ang et al 2019 ). Finally, DLG2 loss has been shown to increase cyclin A2 and result in S phase progression and DNA replication (Keane et al 2020 ), a similar function to the integral inflammasome component GSDMD (Wang et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%